DEVELOPMENT OF TWO-DIMENSIONAL INVERSION MAGNETOTELLURIC DATA WITH OCCAM METHOD - Firmansyah (NIM 20204018), Vera
ABSTRACT: Magnetotelluric data inversion helping to find out under surface structure with real observation data (resistivities, phase, field, and tipper). The first model is needed to compare with observation data for each iteration until minimum misfit value. The last model response is representative of under surface structure. To obtain smooth model, the non-linear forward function is linearized by first model. Electromagnetic data modeling for two-dimensional was constructed using the finite element via Ritz formulation. This method is applied to transverse electric (TE) and transverse magnetic (TM) mode by plane wave source. The solution global matrix equation is solved using iterative solution procedure called conjugate gradient.